Orthographic variation < Macau>/<Macao > and Macau identity - Trin Qingyi Chen; Brian Hok-Shing Chan (Cogent Arts & Humanities, 2024)
This study examines the orthographic variation between the place name <Macau> and <Macao> in English texts in Macau and its interaction with social factors. Using Sebba’s framework of Orthographic Regimes, a statistical analysis was conducted to explore the usage of the two orthographic variants across three levels of orthographic regimes, namely, highly-regulated (HR) government writings, less-regulated (LR) school writings and lesser-regulated (LRR) online texts . As a means to collect data of LR regimes, a questionnaire was used to collect participants’ identities and elicit potential indexical relationships between the two variants and aspects of Macau identity, which we see as two place identities. Results show a strong connection between orthographic regimes and variant usage, with  <Macao >  preferred in HR government writing while Macau is more commonly used in LR regimes where  <Macao>  is not required. Furthermore, this study discusses a connection between language practices and Macau identity based on orders of indexicality, that is, the use of  < Macau>/<Macao >  and the duality of Macau identity (i.e. a nationalistic identity vs. an ethnocultural identity).